Reflections on the mental state of the Polish Armed Forces during the period of restructuring of the Polish Army from a clinical psychology perspective - Terelak, Jan Felicjan (Studia Psychologica: Theoria et praxis, 2002)
The political and economic transformations in progress now for many years in our country have required restructuring of the Polish armed forces. Scientific studies taking into account many perspectives (political, military, organizational, sociological, ethical, psychological and so on), have not yet appeared. The following reflections are an attempt to analyze the mental phenomena accompanying the political and organizational changes in the Polish Army, carried out from a clinical psychology perspective. On the basis of observations by clinical and military psychologists and analysis of media and survey information several syndromes of the mental state of Polish Army personnel in a period of restructuring can be described as for example: “laughing melancholy”, “victims of totalitarianism”, “objectification”, “subjective social injustice”, “amateurism”, “Tower of Babel”, “Byzantine”, “group thinking”, and “culture of passivity”.